Titonia Utilization and The Rest Of Soybean Harvest In The Alternative As Fertilizer Ultisol Fertility Improvement And Soybean Crop Production - Yadi Jufri, Syafrimen Yasin, Agustian, Teguh Budi Prasetyo, Nurhajati Hakim (Universitas Andalas, 2017)
Utilization Titonia and soybean crop residues (straw soybean) as compost, is onealternative fertilizer to improve soil fertility Ultisol. This study aimed to determinethe effect of a mixture of compost and straw Titonia soy, lime and fertilizers inimproving soil fertility and soybean crop production. The research was conductedat experimental field LimauManis and laboratory analysis conducted at theLaboratory P3IN Andalas University, Padang. Research using Random Design(RBD), which consists of 10 treatments with 3 replications were tested. The resultsshowed that administration of lime, compost and fertilizers give effect to thechemical characteristics Ultisol namely against soil pH value, the content of N, Pand K soil. The provision of artificial fertilizers as much as 50% of the soybeancrop needs, provide higher impact than that of artificial fertilizers as much as 25%of the increase in soil fertility and the growth and production of soybean plants.Production of dry seeds of soybean highest weight obtained amounted to 1.85 tons /ha in the treatment of lime dolomite 500 kg / ha + compost mixture (5 tonsTitonia/ha with 5 tons of soybean straw/ha) + NK fertilizers by 50% of the soybeancrop needs (treatment G).